Capital opening: a study in large and average companies in Claudio, MG (Research, Society and Development, 2019)
This paper aimed to identify and analyze why the large and medium-sized companies of the municipality of Claudio, MG, do not open the capital. To achieve the proposed objectives, a multi-case study was carried out in five large and medium-sized companies. This is a descriptive and exploratory research with a qualitative approach, whose information was collected through semi-structured interviews with the owners and managers of the five selected companies. It was noticed that the companies surveyed were familiar, with two of them having only one owner. It was concluded that the companies surveyed did not open capital due to a lack of interest in this type of fund raising, lack of knowledge about the capital market and the processes of IPO and lacking the necessary structure to meet the requirements of the CVM.